Highly efficient fluorescence resonance energy transfer in co-encapsulated BODIPY nanoparticles - Hewavitharanage, Priyadarshine; Steele, Launa; Dickenson, Isaac (European Journal of Chemistry, 2021)
Fluorescence resonance energy transfer (FRET) is a powerful tool used in a wide range of applications due to its high sensitivity and many other advantages. Co-encapsulation of a donor and an acceptor in nanoparticles is a useful strategy to bring the donor-acceptor pair in proximity for FRET. A highly efficient FRET system based on BODIPY-BODIPY (BODIPY: boron-dipyrromethene) donor-acceptor pair in nanoparticles was synthesized. Nanoparticles were formed by co-encapsulating a green emitting BODIPY derivative (FRET donor, lmax = 501 nm) and a red emitting BODIPY derivative (FRET acceptor, lmax = 601 nm) in an amphiphilic polymer using the precipitation method. Fluorescence measurements of encapsulated BODIPY in water following 501 nm excitation caused a 3.6 fold enhancement of the acceptor BODIPY emission at 601 nm indicating efficient energy transfer between the green emitting donor BODIPY and the red emitting BODIPY acceptor with a 100 nm Stokes shift. The calculated FRET efficiency was 96.5%. Encapsulated BODIPY derivatives were highly stable under our experimental conditions.